Pengaruh Kompetensi Pedagogik terhadap Kinerja Guru di Sekolah Islam Terpadu Az-Zahra Kota Gorontalo - Anisa Hamzah; Radia Hafid; Abdulrahim Maruwae; Meyko Panigoro; Yulianti Toralawe (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
This study examined whether pedagogic competence influences teacher performance in the Az-Zahra Integrated Islamic School, Gorontalo City This study used a descriptive quantitative approach on 30 respondents. The instrument used was a questionnaire. The data analysis technique used was simple linear regression analysis. Based on the correlation coefficient test results, the value of the Pearson correlation coefficient was obtained at 0.728. This indicated a strong relationship between pedagogic competence (X) and teacher performance (Y). The results of the determination coefficient test obtained an R-Square value of 0.530, which indicated that 53% of the variability regarding teacher performance can be explained by pedagogic competence and other unexamined variables influence 47%.